Facile synthesis of Ag nanowire-rGO composites and their promising field emission performance - Samantara, Aneeya K.; Mishra, Dillip Kumar; Suryawanshi, Sachin R.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Jena, Bikash Kumar; Rout, Chandra Sekhar (RSC Advances, 2015)
Crystalline, ultra long silver nanowires (Ag NWs), few-layered rGO (reduced graphene oxide) and their rGO-Ag NW nanocomposite have been synthesized using a polyol reflux technique under optimized experimental conditions. The field emission performance of the rGO-Ag NW nanocomposite, rGO and Ag NW emitters was investigated. The turn on field required to draw an emission current density of similar to 1 mA cm(-2) was found to be similar to 5.00, 3.92 and 2.40 V mu m(-1) for the Ag NW, rGO and rGO-Ag NW nanocomposite emitters, respectively. The combined contribution of the sharp edges of the thin graphene sheets and high aspect ratio of the Ag nanowires, and their synergetic effect in the rGO-Ag NW nanocomposite, are responsible for the enhanced field emission behavior. First-principles density functional calculations show that the enhanced field emission may also be due to the overlapping of the electronic structures of the Ag NWs and rGO nanosheets.

Concerted effect of Ni-in and S-out on ReS2 nanostructures towards high-efficiency oxygen evolution reaction - Das, Tapas K.; Ping, Tapan; Mohapatra, Manoj; Anwar, Shahid; Gopinath, Chinnakonda S.; Jena, Bikash Kumar (Chemical Communications, 2022)
Herein, a one-step hydrothermal reaction is developed to synthesize a Ni-doped ReS2 nanostructure with sulphur defects. The material exhibited excellent OER activity with a current density of 10 mA cm(-2) at an overpotential of 270 mV, a low Tafel slope of 31 mV dec(-1), and good long-term durability of 10 h in 1 M KOH. It shows high faradaic efficiency of 96%, benefiting from the rapid charge transfer caused by the concerted effect of Ni-in and S-out on the ReS2 nanostructure.